Letter of Credit Related Trade Disputes - Court Decisions Legal Certainty In Indonesia - Achir, Rori; Farma Rahayu, Mella Ismellina; Sudiro, Ahmad (UI Scholars Hub, 2024)
This study examines the legal certainty surrounding commercial letters of credit (L/C) within the context of Indonesian judicial practice, focusing on how courts conduct hearings and render decisions in L/C-related trade disputes. The term “L/C” in this research encompasses both international L/C and the domestic equivalent, Surat Kredit Berdokumen Dalam Negeri (SKBDN). The analysis explores whether Indonesian courts have undertaken comprehensive judicial examinations across five key dimensions: (1) the determination of whether a breach of contract or a tort occurred; (2) the characterization of contractual relationships among the disputing parties; (3) the application of the L/C independence principle; (4) the interpretation of L/C clauses and governing provisions; and (5) the assessment of documentary evidence. The study further compares decisions across cases with similar factual or legal characteristics, as well as among courts of different hierarchical levels, to evaluate the consistency of judicial reasoning and outcomes. The findings indicate that judicial considerations and decisions have not yet established a robust sense of legal certainty regarding L/C transactions in Indonesia. Consequently, the study recommends the formulation of clear regulatory provisions to guide both commercial parties and the judiciary in addressing L/C-related legal issues and adjudicating trade disputes.